2006
DOI: 10.1071/ea03157
|View full text |Cite
|
Sign up to set email alerts
|

Yield and economic benefits of common bean (Phaseolus vulgaris) and soybean (Glycine max) inoculation in northern Tanzania

Abstract: On-farm experiments were conducted in farmers’ fields at 12 different sites in the 2 districts of Moshi and Rombo in northern Tanzania during the 2000–01 cropping season to study the effects of (brady)rhizobial inoculation in combination with P supply on growth and grain yields of soybean and common bean, and to assess the economic returns of these different technologies to farmers. A low level of N was included as an indicator of endogenous soil N status. The treatments included (brady)rhizobial inoculation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 22 publications
1
82
0
Order By: Relevance
“…This seems to be an important reason for its low seed yield in Ethiopia. This constraint could be alleviated through seed and/or soil inoculation with the proper Rhizobium bacteria before or at planting to facilitate N-fixation (Ndakidemi et al, 2006). Therefore, to increase the productivity of the farmers, it is crucial to increase the awareness of farmers towards the utilization of improved agronomic practices that increase their production and accelerate food security through proper implementation.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be an important reason for its low seed yield in Ethiopia. This constraint could be alleviated through seed and/or soil inoculation with the proper Rhizobium bacteria before or at planting to facilitate N-fixation (Ndakidemi et al, 2006). Therefore, to increase the productivity of the farmers, it is crucial to increase the awareness of farmers towards the utilization of improved agronomic practices that increase their production and accelerate food security through proper implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at Lyamungu on the lower slopes of Kilimanjaro in northen Tanzania also showed the benefits of inoculation but best yields were obtained when inoculation was combined with a dressing of 40 kg/ha of phosphorus and without nitrogen (Sachansky, 1977;Ndakidemi et al, 2006). In further experiments it was demonstrated that cultivars bred and selected in Tanzania were compatible with native Rhizobium spp.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, the recent industrial conversion of composted organic materials into value-added single product as plant growth promoter through a novel approach of enrichment or blending of bio-fertilizers with inorganic fertilizers or plant growth promoting rhizobacteria (Tahir et al, 2006), constitute an alternative strategy for increased use of organic fertilizers. The use of such biological growth promoter has been reported to considerably increase grain yield (Ndakidemi et al, 2006;Kutu and Asiwe, 2010).…”
Section: Introductionmentioning
confidence: 99%